Antología del grabado del sur peruano Primer panorama del grabado en el interior del país - Mendoza Laura, Helberth (2020)
The plastic production of engraving beyond Lima it has been uncertain and known in a lot of time, is in the year 2003 that arises an annual sample of engraving in Cusco that progressively it has grouped artists and related schools of art of diverse regions of the country, for more than fifteen years. in 2015 all these efforts were summarized on the exhibition entitled “ANTHOLOGY OF THE ENGRAVING OF THE PERUVIAN SOUTH” The present article it approaches the analysis of the sample that offered a wide and varied panorama of one of the most significant artistic expressions of the south of Peru, which summarizes the works of the great masters of southern contemporary engraving. Exhibited at the Inca Garcilaso Cultural Center of the Ministry of Foreign Affairs in Lima in March and May 2015. The importance of the study consists of showing the development and impact achieved with the exhibition.